Improving Bing Web Search using Azure GPUs - presented at SC19 - Zhu, Jeffrey; Li, Mingqin (Presented at SC19, 2019)
Presentation slides on Improving Bing Web Search using Azure GPUs given by Jeffrey Zhu and Mingqin Li.